Convict Depot - Carrera Isle - Trinidad - (:unkn) unknown (Bonanza Smith Bros. and Co.,[Trinidad and Tobago];Printed in Germany, 2011)
The postcard shows Carrera Island, referred to as Convict Depot because during the 1800s prisoners were carried to the island to quarry limestone for road building. In 1877, a prison was constructed, today the island remains a prison island. The postcard is addressed to Mr. George Konghaki of New York, United States of America and affixed is a penny Trinidad and Tobago postage stamps, while the card is dated 1914.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; 1914; Prisons--Trinidad and Tobago; Islands--Trinidad and Tobago; Carrera Island